STRATEGI MANAJEMEN SDM DALAM MENCEGAH PENIPUAN PEREKRUTAN: ANALISIS KASUS GDPS - Harmen, Hilma; Azzahra Siregar, Nabila Kesya; Rahman, Rahman; Alfarisi, Mhd Rasyid; Br Tarigan, Ayu Primsa; Br Sebayang, Dira Febrina; Atikah, Dhiya; Pulungan, Raamadhan (Growth, 2025)
Fraud in employee recruitment is a challenge for companies like GDPS. The research aims to analyze GDPS's strategy in managing fraud risk through HR management. Using a qualitative approach and data obtained through a literature review, this research assesses the policies, procedures and technology implemented by the company. Findings show that verification technology, strict selection, and education are effective in reducing fraud. GDPS also utilizes AI and blockchain to verify candidate identities, as well as a multi-layered selection process to ensure the authenticity of applicants. This research offers new insights into the application of technology to prevent fraud in recruitment.